2019
DOI: 10.1080/08998280.2019.1625660
|View full text |Cite
|
Sign up to set email alerts
|

Association between psychological resilience and subjective well-being in older adults living with chronic illness

Abstract: We aimed to determine the impact of resilience on well-being in chronically ill adults, hypothesizing that resilient participants would have higher quality of life, life satisfaction, and happiness and less psychological distress than those with low resilience. Patients who received treatment for a chronic illness at Baylor Scott & White Health and self-identified an informal caregiver (nonpaid friend/family member who provides regular care) were eligible. After the Center for Community Research and Developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 24 publications
5
40
1
5
Order By: Relevance
“…Resilient healthcare professionals can preserve a positive outlook towards the patients, fulfil their duties realistically, and have effective strategies to reduce stress despite these challenges (Stevenson et al 2011). In wider literature, resilience has been found to be a strong predictor of psychological distress and quality of life (Tecson et al 2019) and subjective, psychological well-being, and mental health (Yıldırım 2019). Previous research has also identified mediator role of resilience between various psychological factors and subjective well-being and psychological health in the context of COVID-19 (Yıldırım and Arslan 2020), suggesting that resilience can be a great source of mental health as it buffers the detrimental effects of stress on psychological health (Ong et al 2006).…”
mentioning
confidence: 99%
“…Resilient healthcare professionals can preserve a positive outlook towards the patients, fulfil their duties realistically, and have effective strategies to reduce stress despite these challenges (Stevenson et al 2011). In wider literature, resilience has been found to be a strong predictor of psychological distress and quality of life (Tecson et al 2019) and subjective, psychological well-being, and mental health (Yıldırım 2019). Previous research has also identified mediator role of resilience between various psychological factors and subjective well-being and psychological health in the context of COVID-19 (Yıldırım and Arslan 2020), suggesting that resilience can be a great source of mental health as it buffers the detrimental effects of stress on psychological health (Ong et al 2006).…”
mentioning
confidence: 99%
“…This could act as a challenge in coping up with the adversity and pose a threat to positive mental health. Prior research demonstrates the negative effect of perceived distress on subjective psychological well-being (Jiang 2020;Meng and D'Arcy 2016;Tecson et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, resilience is associated with both positive and negative mental health (Shapero et al 2019;Srivastava 2011). Resilience has revealed to result in lowering symptoms of negative mental health (Tecson et al 2019). Further, researches indicated that resilience enhances positive mental health (Cuhadar et al 2016;Vieselmeyer et al 2017) in particular subjective well-being (Satici 2016;Tecson et al 2019; Yildirim and Arslan 2020) and it acts as a protective factor (Sera ni 2020).…”
Section: Perceived Distress and Subjective Psychological Well-being: mentioning
confidence: 99%
See 1 more Smart Citation
“…Since patients with heart failure usually suffer repeated crises, resilience for managing and overcoming these is important (Kralik, van Loon, & Visentin, 2006). Resilience to overcome crises and adversity and to perform adaptive functions (Masten, 2001), can be strengthened by external help or education (Grafton, Gillespie, & Henderson, 2010) and improved well-being in adults with chronic disease (Tecson, Wilkinson, Smith, & Ko, 2019). Coronary artery disease patients with higher resilience showed higher health-promoting behaviors (Cheon & Kang, 2016), and hypertension patients showed similar results; the higher the resilience, the higher the self-care capacity (Jeong, Lee, & Kim, 2017).…”
Section: Introductionmentioning
confidence: 99%